Kajian Geometri Jalan Tambang untuk Meningkatkan Produksi Penambangan Andesit PT Gunung Kulalet Kecamatan Baleendah, Kabupaten Bandung, Provinsi Jawa Barat - Rijal Aditya Prasetya; Zaenal; Noor Fauzi Isniarno (UNISBA Press, 2022)
Abstract. This mining road evaluation activity is carried out with the aim of knowing the condition of the road geometry used as well as efforts to improve road geometry and production before repairing and after repairing the mining road including straight road width, bend road width, road slope, bend radius, superelevation, transverse slope, and the actual rimpull. This research was conducted using primary and secondary data collection methods, data processing techniques and data analysis techniques, which were compared with the standards in Decree No. 1827/K/30/MEM/2018 and AASHTO in an effort to increase mining production. Based on the results of the research, the actual width of the straight road is between 3,95 – 12,90 meters and the width of the bend road is 5,13 – 9,77 meters. For the road slope, the grade varies from 1,596% - 37,35% with a maximum standard grade of 12% so that there are 4 road segments that are repaired. The actual superelevation condition starts from 13,55% - 38,56% based on the calculation of the minimum superelevation is 6% so that repair simulations are carried out on each superelevation segment. Based on the results of calculations regarding production before repair of loading equipment of 81,61 BCM/hour and transportation equipment of 81,58 BCM/hour, with the company's production target of 100 BCM/hour. After simulating the improvement of road geometry, the production after repair of loading equipment was 105,91 BCM/hour and transportation equipment of 105,74 BCM/hour. The increase in production occurs because the circulation time of the conveyance is getting faster, where before the repair the cycle time is 13.03 minutes, while after the simulation the repair is 8.01 minutes. Abstrak. Kajian jalan tambang ini dilakukan dengan tujuan mengetahui produksi sebelum perbaikan geometri jalan tambang. Kemudian mengetahui upaya perbaikan geometri jalan tambang berdasarkan kesesuaian pada Kepmen No. 1827/K/30/MEM/2018 dan AASHTO dalam upaya mencapai target produksi. Tujuan selanjutnya mengetahui produksi dari alat muat dan alat angkut yang didapatkan setelah perbaikan geometri jalan tambang. Adapun geometri jalan tambang meliputi lebar jalan lurus, lebar jalan tikungan, kemiringan jalan, jari-jari tikungan, superelevasi, kemiringan melintang. Berdasarkan hasil penelitian kondisi lebar jalan lurus aktual berkisar antara 3,95 – 12,90 meter dan lebar jalan tikungan sebesar 5,13 – 9,77 meter. Kemiringan jalan memiliki grade bervariasi dimulai dari 1,596% - 37,35% dengan standar grade maksimal sebesar 12%. Kondisi superelevasi aktual dimulai dari 13,55% - 38,56% berdasarkan perhitungan superelevasi minimum adalah 6%, sehingga dilakukan simulasi perbaikan pada setiap segmen superelevasi. Berdasarkan hasil perhitungan mengenai produksi sebelum perbaikan alat muat sebesar 81,61 BCM/jam dan alat angkut sebesar 81,58 BCM/jam, dengan target produksi perusahaan sebesar 100 BCM/jam. Setelah dilakukan simulasi perbaikan geometri jalan didapatkan produksi alat muat sebesar 105,91 BCM/jam dan alat angkut sebesar 105,74 BCM/jam. Peningkatan produksi terjadi karena waktu edar dari alat angkut yang semakin cepat, dimana saat sebelum perbaikan waktu edarnya 13,03 menit, sedangkan setelah dilakukan simulasi perbaikan menjadi 8,01 menit.